Pesky metrics: the challenges of measuring ART adherence among HIV-positive adolescents in South Africa. Issue 2 (14th March 2020) - Hodes, Rebecca; Cluver, Lucie; Toska, Elona; Vale, Beth
ABSTRACT: The global rollout of antiretroviral treatment (ART) for HIV is one of the largest public health interventions ever undertaken. As the rollout expands, a growing body of research has focused on adherence to ART: how is it measured, what are the flaws of these metrics, and how may these be improved? We provide an overview of current, critical developments in adherence research among adolescents, and of how research on adherence to ART among adolescents within hyper-epidemic contexts has challenged definitions and measurements of adherence. We then explore the development of adherence metrics within an interdisciplinary study about HIV-positive adolescents: the Mzantsi Wakho study. Tracing the conceptualisation and adaptation of adherence metrics within this study, we examine how qualitative and quantitative approaches may be combined to establish more comprehensive adherence metrics. Findings highlight the challenges and the imperatives of synthesising numerous methods, data points, and temporalities. They also point to the need for researchers to establish direct and continued participation by adolescents themselves to better conceptualise and measure adherence, as well as other health behaviours.